2021
DOI: 10.1108/er-12-2020-0522
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employment relationships on firm sustainability

Abstract: PurposeThe aim of this study was to analyse the influence of different employment relationships (ERs) on the sustainability results of cooperatives. The authors approached the type of ER comparing the inducements offered by the firm with the contributions that the manager expects from employees. In this way, the authors study how the orientation toward the employment relationship influences the economic, social and environmental sustainability of the firm.Design/methodology/approachThis article presents a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These people are needed to generate innovative ideas and development through effective communication based on management conveying complete, accurate and clear information. If employees have all the necessary information and answers to their questions from the management of their organization, their loyalty is built, as confirmed by the study [ 13 ]. As the research has shown, top-down internal communication can take many forms, ranging from written and visual to electronic and oral communication, which the Bata Management System emphasized.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…These people are needed to generate innovative ideas and development through effective communication based on management conveying complete, accurate and clear information. If employees have all the necessary information and answers to their questions from the management of their organization, their loyalty is built, as confirmed by the study [ 13 ]. As the research has shown, top-down internal communication can take many forms, ranging from written and visual to electronic and oral communication, which the Bata Management System emphasized.…”
Section: Resultsmentioning
confidence: 83%
“…Maintaining and developing relationships in the workplace and among team members is a trend not only in human resource management. Building relationships among all employees, fostering the maintenance and development of a positive individual [ 1 ], corporate culture [ 12 ] and teamwork relationships [ 13 ] are important factors for cohesion and deepening the intention of individuals to remain in an organization that is based on good relationships and a sense of belonging.…”
Section: Introductionmentioning
confidence: 99%
“…They encourage individuals to freely express their thoughts, share their vision and contribute innovative ideas within the organization thereby fostering a creative and dynamic work environment. It is highly recommended that the leadership of hotels should place a strong emphasis on fostering employee creativity (Rincon-Roldan and Lopez-Cabrales, 2022). The proficient staff members of hotels equipped with their extensive expertise and appropriate levels of motivation have the capacity to create and generate a multitude of creative ideas and recommendations for the effective execution of sustainability efforts.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%